Remittance trap: comparative approach of the Republic of Moldova and other ex-socialist countries - Elina BENEA-POPUȘOI; Polina ARIVONICI (Eastern European Journal of Regional Studies, 2021)
Abstract: The objective of our analysis has been to find out and elaborate on why some countries could not benefit from remittance inflows sent by migrants or even are getting into traps due to them. In the authors’ view, the remittance trap may be appraised, notably in the long run, as the dilemma in which a country finds itself when the high value of migrant remittance inflows leads to a high value of human and financial capital outflows, as well as to the moral hazard problem of the country's population and government. Accordingly, remittance trap negatively affects the sustainable growth and development of the economy which eventually deepens the country's dependence on remittances, proving the vicious nature of the trap. Furthermore, the paper focuses on identifying a competent set of policy recommendations for the countries that are remittance dependent. A natural conclusion of our research is that there is a thin line between remittances’ advantages and disadvantages, since in fact, short-term benefits very often turn out into long-run side effects, mainly as a result of mismanagement of remittance inflows, which correlates with unfavourable business climate and decreased willingness of the population to invest. Accordingly, the benefits and adverse side effects of remittance inflows are interdependent.